Safety, tolerability, and immunogenicity of 15-valent pneumococcal conjugate vaccine in healthy adults. Issue 24 (4th June 2015) - McFetridge, Richard; Meulen, Ajoke Sobanjo-ter; Folkerth, Steven D.; Hoekstra, John A.; Dallas, Michael; Hoover, Patricia A.; Marchese, Rocio D.; Zacholski, Donna M.; Watson, Wendy J.; Stek, Jon E.; Hartzel, Jonathan S.; Musey, Luwy K.
Abstract: Background: Pneumococcal disease remains an important health priority despite successful implementation of pneumococcal conjugate vaccines (PCVs) in infant immunization programs, mainly due to the emergence of diseases caused by serotypes not included in licensed PCVs. A 15-valent pneumococcal conjugate vaccine (PCV-15) containing the 7 serotypes (4, 6B, 9V, 14, 18C, 19F, and 23F) included in licensed PCV-7 available at study initiation plus 8 additional serotypes (1, 3, 5, 6A, 7F, 19A, 22F, 33F) was developed and evaluated in healthy adults 18–45 years of age. Methods: Sixty subjects received one dose of PCV-15 or PCV-7. Injection-site and systemic adverse events (AEs) were collected for 14-days postvaccination and serious AEs were collected for 30-days postvaccination. Safety laboratory tests (hematology, chemistry, and urinalysis) were evaluated prior to vaccination and 14-days postvaccination. Serotype-specific IgG and opsonophagocytic killing activity (OPA) responses to 15 serotypes included in PCV-15 were measured immediately prior to vaccination and 30-days postvaccination. Results: AE incidences were comparable between vaccine groups although numerically higher frequencies of erythema (33.3% versus 13.3%), swelling (50.0% versus 23.3%), and myalgia (63.3% versus 36.7%) were reported among PCV-15 versus PCV-7 recipients. Majority of AEs, irrespective of vaccine received, were transient and of mild-to-moderate intensity. No clinically significant differences were observed when comparing AE duration and severity. No laboratory abnormalities, vaccine-related SAEs or discontinuations from the study due to AEs were reported. IgG concentrations for the shared serotypes substantially increased postvaccination at comparable levels between recipients of PCV-15 and PCV-7. Substantial increases in antibody (IgG and OPA) responses to 8 serotypes unique to PCV-15 were observed in PCV-15 recipients. Slight increases to 2 serotypes unique to PCV-15, serotypes 6A and 19A, were also noted in PCV-7 recipients. Conclusion: PCV-15 displays an acceptable safety profile and induces IgG and OPA responses to all serotypes included in the vaccine.